2020
DOI: 10.1002/ijgo.13140
|View full text |Cite
|
Sign up to set email alerts
|

HE4 tumor marker as a predictive factor for lymphatic metastasis in endometrial cancer

Abstract: Endometrial cancer is the most common genital cancer in high-resource countries.Treatment is essentially surgical, but the role of lymphadenectomy in the treatment of low-stage and low-grade tumors has not been defined. Although no tumor factors have been validated for use as preoperative prognostic markers of endometrial cancer at yet, human epididymis protein 4 (HE4) has received much interest as a potential diagnostic and prognostic tumor marker. Since 2008, several studies have explored its utility in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…To compare the diagnostic value of the studied AFs with biomarkers that are in clinical use, we compared the ROC curves for sTie-2, G-CSF, and leptin with those for CA-125 and HE4. CA-125 and HE4 have been extensively studied in ovarian and EC, and their diagnostic and prognostic values in gynecological cancers have been reported [16,[55][56][57]. This comparison revealed that sTie-2, G-CSF, and leptin have similar AUC values as CA-125 and HE4 for the separation of EC and control patients.…”
Section: Discussionmentioning
confidence: 84%
“…To compare the diagnostic value of the studied AFs with biomarkers that are in clinical use, we compared the ROC curves for sTie-2, G-CSF, and leptin with those for CA-125 and HE4. CA-125 and HE4 have been extensively studied in ovarian and EC, and their diagnostic and prognostic values in gynecological cancers have been reported [16,[55][56][57]. This comparison revealed that sTie-2, G-CSF, and leptin have similar AUC values as CA-125 and HE4 for the separation of EC and control patients.…”
Section: Discussionmentioning
confidence: 84%
“…Endometrial lesions are common gynecological diseases, which have a great impact on women's physical and mental health and quality of life. In particular, endometrial cancer is one of the most common gynecological malignancies (1)(2)(3)(4)(5) and accounts for 20%-30% of malignant tumors of the female reproductive tract (6). The prognosis of early endometrial cancer patients is generally good, with a 5-year survival rate of >90% for Stage IA disease (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly expressed in the serum of patients with malignant tumors but may be increased in varying degrees in the serum of benign lesions or healthy patients. HE4 has been recently identified as a potential biomarker in endometrial carcinoma (3,4,27,28). Some studies (3,5,(29)(30)(31)(32)(33) showed that CA125 and HE4 were significantly correlated with histological grade, stage, lymph node metastasis, muscular invasion, and cervical involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus on the possible application of HE4 as a preoperative marker for the endometrioid subtype of endometrial cancer and results are heterogeneous. However, there seems to be a correlation between endometrial cancer prognostic factors and preoperative HE4 levels 9‐11 …”
Section: Introductionmentioning
confidence: 99%
“…However, there seems to be a correlation between endometrial cancer prognostic factors and preoperative HE4 levels. [9][10][11] Some studies do not take into account the histologic subtype of endometrial cancer, although there is evidence of substantial differences in patient prognosis regarding the histologic subtype. 12,13 A preoperative tumor marker that can predict advanced stage or nodal metastasis could be helpful in planning a more individualized surgical procedure in endometrioid endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%